The nexus between blockchain distributed ledger technology and financial crimes - Newton Chinyamunjiko; Forbes Makudza; Lucia Mandongwe (Goodwood Publishing, 2023)
Purpose: The study sought to uncover the effect of blockchain digital ledger technology (BCDLT) on financial crimes. The study was driven by the need to promote blockchain technology in a bid to enhance financial sanity through elimination of financial delinquency.